Why asymmetric molecular coupling to electrodes cannot be at work in real molecular rectifiers - Bâldea, Ioan (Physical review, 2021)
Every now and then one hears in the molecular electronics community that asymmetric couplings (Γs≠Γt) of the dominant level (molecular orbital) to electrodes (s and t) which typically have shapes different from each other may be responsible for current rectification observed in experiments. Using a general single level model going beyond the Lorentzian transmission limit, in this work we present a rigorous demonstration that this is not the case. In particular, we deduce an analytical for the bias (V)-driven shift of the level energy δɛ0(V) showing that δɛ0(V)/V scales as Γt/Wt−Γs/Ws, which is merely a tiny quantity because the electrode bandwidths Ws,t are much larger than Γs,t. This result invalidates a previous, never deduced formula used in some previous publications that neither could be justified theoretically nor is supported by experiment. Toward the latter aim, we present new experimental evidence adding to that already inferred in earlier analyses.